Knockdown of REGγ inhibits the proliferation and migration and promotes the apoptosis of multiple myeloma cells by downregulating NF-κB signal pathway. Issue 5 (28th May 2018) - Liu, Shuang; Zheng, Li-ling; Zhu, Yang-min; Shen, Hui-juan; Zhong, Qi; Huang, Jing; Li, Cheng; Liu, Zhi; Yao, Meng-dong; Ou, Rui-ming; Zhang, Qing
ABSTRACT: Objectives: This study aimed to evaluate the effects of REGγ knockdown on the proliferation, apoptosis and migration of multiple myeloma (MM) cells, and reveal the potential regulatory mechanisms. Methods: The expression of REGγ on myeloma cells of 28 MM patients was detected by Western blot. shRNA-REGγ-1 and shRNA-REGγ-2 were constructed to downregulate REGγ in RPMI-8226 cells. The proliferation, apoptosis and migration of transfected cells were analyzed by Cell Counting Kit 8 (CCK8), flow cytometry and transwell chamber, respectively. The expression of phosphorylated p65 (p-p65), p65, NF-kappa-B inhibitor ε (IkBε), matrix metalloproteinase 2 (MMP2), B-cell lymphoma xL (Bcl-xL) and X-linked inhibitor of apoptosis protein (XIAP) in transfected cells was detected by Western blot. Using cycloheximide (CHX), the half-life period of IkBε was detected by Western blot. Results: The expression of REGγ was positive in myeloma cells. The proliferation and migration of RPMI-8226 cells were significantly inhibited by shRNA-REGγ-1/shRNA-REGγ-2, while the apoptosis rates were significantly increased ( p < 0.05). The expression of p-p65 and IkBε was significantly reduced in RPMI-8226 cells transfected with shRNA-REGγ-1/shRNA-REGγ-2. The degradation of IkBε was significantly lower in RPMI-8226 cells transfected with shRNA-REGγ-1 than the control (longer half-life period). Besides, the expression of MMP2, Bcl-xL and XIAP in RPMI-8226 cells was significantly inhibited by shRNA-REGγ-1/shRNA-REGγ-2. Discussion: Knockdown of REGγ may inhibit the proliferation and migration, and promote the apoptosis of RPMI-8226 cells possibly by downregulating NF-κB signal pathway.